The dichotomous impacts of Semaphorin3E deficiency on exacerbating airway hyperresponsiveness, remodelling, and inflammation in type-2 low and type-2 high asthma models - Mojdeh Matloubi; Fatemeh Sedaghat; Lianyu Shan; Sujata Basu; Andrew J. Halayko; Abdelilah S. Gounni (PLoS ONE, 2025)
Semaphorin3E has shown promise in alleviating the severity of asthma in preclinical studies; however, its role in the chronic features of type 2-low asthma remains unclear. Therefore, we aimed to investigate the role of Sema3E in a mouse model of severe asthma that exhibits a mix of granulocytic inflammation with neutrophils dominance and compared the results with those from the type-2 high eosinophilic asthma model. Sema3E knockout (KO) and wild-type (WT) mice were subjected to type-2 low and type-2 high regimens using house dust mite (HDM) combined with cyclic-di-GMP or HDM alone, respectively. Airway hyperresponsiveness parameters were measured using the FlexiVent ventilator. Bronchoalveolar lavage fluid cell phenotyping was performed by flowcytometry. Additionally, cytokines and antibodies were quantified using Mesoscale and ELISA. Mucus overproduction and goblet cell hyperplasia were visualized by Periodic-acid–Schiff staining. In comparison to WT mice, Sema3E KO mice exhibited an enhanced tissue resistance and tissue elastance in the type 2-low asthma model. Concurrently, Sema3E KO mice that were subjected to the type-2 low asthma model demonstrated an elevated presence of pulmonary neutrophils, dendritic cells, CD4 T cells, as well as increased levels of IL-17, TNF, IL-1β, CXCL-8, and MCP-1/CCL2 in comparison to their WT counterparts. However, in the type-2 high model, Sema3E KO mice exhibited a significant increase in goblet cell numbers and mucus overproduction, as well as enhancements in the number of eosinophils, IgE-producing B cells, and IL-4 levels compared to WT mice, highlighting the homeostatic role of Sema3E in the distinct immune niche of type-2 low and type-2 high asthma. Overall, our data showed that Sema3E is critical in modulating AHR, airway inflammation, and tissue remodelling in type 2 low and type 2 high phenotypes of asthma. The Sema3E regulatory network varies depending on the immunization regimen, affecting distinct parameters in type-2 low and type-2 high asthma models.